Developing English learning materials for grade eight students at IOs International Education Yogyakarta - Sari, Ary Diah Puspita; Priyana, Joko (LingTera, 2021)
This research aims to develop English learning materials for grade eight students at IOs International Education. This research adopted the material development procedure proposed by Graves (2000: 105) and Dick, Carey and Carey (2005:1). The data were collected by using observation sheets and questionnaires. The data were quantitative and qualitative data. The quantitative data were analyzed using descriptive statistics, while the qualitative data were analyzed qualitatively. The results of this study are four units of learning materials. Each unit consists of 18 to 20 tasks. Each unit is organized into six components namely introductory page, warm-up, main tasks (spoken cycle and written cycle), summary, evaluation, and glossary. The research results show that the developed course materials of English for grade eight obtained a score of 4.414 (very good). Then, the students' try-out results obtained 4.47 (very good). These results show that the developed English course materials of English for eighth grade students in IONs International Yogyakarta are appropriate.